The significance of responsible tourism as an approach for sustaining cultural heritage values: a case study of Georgetown, Penang - Mohd Fadzly, Jihan Tsara; Ghani, Izham (2025)
The study explores Responsible Tourism as an approach to balance the growth of the tourism industry with the preservation of Georgetown cultural history, a UNESCO World Heritage Site, due to the growing concern over the sustainability of cultural assets in heritage-rich locations. The impact of mass tourism on local communities and heritage sites, as well as the necessity of increased community engagement in tourism management, are among the important concerns covered in the research. The main objectives of the research are to explore the role of Responsible Tourism in enhancing cultural heritage preservation, promote community engagement in tourism-related activities, and propose strategies to mitigate the negative effects of tourism. A number of important topics are covered in this study, such as how tourism affects cultural heritage, and the necessity of Responsible Tourism practices that respect cultures. The study uses a structured questionnaire to locals approach for quantitative surveys. The results show that incorporating Responsible Tourism into cultural heritage promotes environmental stewardship and cultural resilience in addition to improving the visitor experience. This study emphasises how crucial it is to acknowledge Responsible Tourism as a key element in the growth of cultural heritage, promoting policies that balance financial gains with cultural sustainability.